BETA-BLOCKERS IN THE TREATMENT OF ARTERIAL HYPERTENSION: EVIDENCE BASED DATA AND REAL PRACTICE - M. V. Leonova (Столичная издательская компания, 2015)
Data of the largest meta-analyzes of beta-blockers use in arterial hypertension is presented. The role of beta-blockers among other basic groups of antihypertensive drugs (thiazide diuretics, calcium channel blockers, ACE inhibitors) is evaluated. Special considerations of beta-blockers use in hypertensive patients with diabetes mellitus and chronic heart failure are discussed. Special attention is paid to bisoprolol.